Studi Keamanan Internasional Pasca Perang Dingin - Umar Suryadi Bakry (Jurnal Alternatif - Jurnal Ilmu Hubungan Internasional, 2022)
This paper is intended to explain the conceptual developments in International Security Studies after the end of the Cold War. Since the end of the Cold War, there has been something of a paradigm shift in both International Relations and International Security Studies. First, there was a ‘widening’ or ‘broadening’ of the subject area of International Security Studies. International Security Studies is no longer focused on issues of conflict, nuclear weapons, and military strategy of the big powers, but has been widened and broadened on the issues that are marginalized by various high-level diplomacy during the Cold War era, such as environmental degradation, economic security, scarcity of energy and other natural resources, the problem of infectious diseases, and others. Second, there was also a trend towards ‘deepening’ in International Security Studies. This referred to the shift of emphasis away from the security of the national state towards a greater concern for the security of the individual. This shift in focus has given rise to increasing interest in the topics of 'human security', as well as a recognition that during the application of the concept of 'national security' that glorified many countries did not cover or protect the security of individual.